They say/I say - Graff, Gerald
They Say / I Say demystifies academic writing by identifying its key rhetorical moves, the most important of which is to summarize what others have said ("they say") to set up one's own argument ("I say"). The book also provides templates to help students make these key moves in their own writing. This version includes readings that demonstrate those moves―and provide stimulating conversations for them to enter. The Second Edition includes an anthology of 44 readings that will provoke students to think―and write―about five important issues, including two new ones: Is Higher Education Worth the Price? and Why Does It Matter Who Wins the Big Game?